Analysis of Regional Independence of Palu City Central Sulawesi Province of 2019-2023 Period - Mulkifli Mulkifli; Musdayati Musdayati; Edhi Taqwa; Andi Herman Jaya; Nuryana Haprin (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
This study focuses on the problem of limited autonomy in regional finances, as regions continue to depend heavily on funds allocated by the central government. This research aims to analyze Regional Original Income in an effort towards regional independence. The analytical method used is a descriptive method using quantitative data sourced from the Palu City Central Statistics Agency in the 2019-2023 research period. The analytical tools used are the Independence Ratio, Effectiveness Ratio and Degree of Fiscal Autonomy formulas. Based on calculations and analysis, the results obtained show that the Palu City Regional Financial Independence Ratio for the 2019-2023 period is classified in the medium category (25.70%). This shows that the regional financial independence of the City of Palu, although still low, indicates progress, even though the regional finances of the City of Palu are still very dependent on the components of Transfer Funds and Other Legitimate Income. In accordance with the assessment criteria for the level of effectiveness of the Palu City government's revenue, it is included in the effective category (112.75%). This is demonstrated by the PAD realization figure exceeding the PAD value targeted by the Palu City Government. The analysis of the value obtained for the Degree of Fiscal Independence for the City of Palu for the 2019-2023 period are in the medium criteria (20.16%). In other words, although regional spending still depends on Transfer Funds and Other Legal Revenue Funds, the financial independence of the City of Palu is increasingly showing a significant increase.